The protective effects of flavonoids and carotenoids against diabetic complications—A review of in vivo evidence - Jin, Yannan; Arroo, Randolph (Frontiers in Nutrition, 2023)
Diabetes mellitus is a chronic metabolic disorder caused either by inadequate insulin secretion, impaired insulin function, or both. Uncontrolled diabetes is characterized by hyperglycemia which over time leads to fatal damage to both macro- and microvascular systems, causing complications such as cardiovascular diseases, retinopathy and nephropathy. Diabetes management is conventionally delivered by pharmacological treatment, using antidiabetic drugs, and modifications of diet and lifestyles, or ultimately insulin injections. However, the side effects and financial cost of medications often reduce patient compliance to treatment, negatively affecting their health outcomes. Natural phytochemicals from edible plants such as fruits and vegetables and medicinal herbs have drawn a growing interest among scientific research in exploring their therapeutic efficacy in treating diabetes and preventing the onset and progression of diabetic complications. Flavonoids, the most abundant polyphenols in human’s diet, have shown antidiabetic effects in numerous in vitro and preclinical studies. The underlying mechanisms are related to their antioxidant, anti-inflammatory and immunomodulatory activities. Carotenoids, another group of phytochemicals are comparatively less studied than flavonoids, but have also presented antidiabetic potential in recent in vitro and in vivo experimental models, whilst sharing the similar mechanistic basis of actions to that of flavonoids. However, scientific evidence on the efficacy of these phytochemicals in treating diabetes and preventing the onset and progression of its complications in clinical settings is scarce, which delays the translation of animal study evidence to human applications and also limits the knowledge on their modes of actions in diabetes management. This review is aimed to highlight the potential roles of flavonoids and carotenoids in preventing or ameliorating diabetes-related complications based on in vivo study evidence, i.e. an array of preclinical animal studies and human intervention trials. The underlying mechanisms of action exerted by both groups of phytochemicals will also be reviewed.